The design of a software architectural framework for tunnelling metering protocols over TCP/IP and low bandwidth packet switched networks with support for proprietary addressing - Hancke, Gerhard P. (University of Pretoria, 2013)
Dissertation (MEng (Computer Engineering))--University of Pretoria, 2008.